Determinants of incomplete immunization among 12–23 months old children in Ethiopia: A multilevel analysis - Sofiya Ayalew Kebede; Yawkal Tsega; Niguss Cherie; Asressie Molla; Chad Stecher (PLoS ONE, 2025)
Background Vaccinations saved over 37 million lives between 2000 and 2019. Despite this, Ethiopia’s Expanded Program of Immunization has struggled to meet its goals, and little has been studied on the community and individual level determinants of incomplete immunization. Therefore, this study aimed to assess the predictors of incomplete immunization among Ethiopian children aged 12–23 months using Ethiopian Mini Demographic Health Survey 2019 (EMDHS 2019). Methods The study used data from EMDHS 2019 and about 1029 children aged 12–23 months were included in the study. STATA version 17.0 statistical software was used to manage and analyze data. Multilevel binary logistic regression analysis was conducted. An AOR with 95%CI, and P < 0.05 were used to determine strength of association and declare significance level, respectively. Results The factors maternal age ranges of 15–24 (AOR: 4.23; 95%CI: 2.17–8.26) and 25–34 (AOR: 2.68; 95%CI: 1.56–4.61), family size ≥5 (AOR: 2.03; 95%CI: 1.24–3.30), ≤3 antenatal care visits (AOR: 2.32; 95%CI: 1.43–3.75), no postnatal care (AOR: 2.20; 95%CI: 1.23–3.95), rural residence (AOR: 2.54; 95%CI: 1.08–6.25), low (AOR=3.55; 95% CI: 1.32–9.55) and moderate (AOR: 3.29; 95% CI: 1.55–7.00) community-level antenatal care services utilization, and low community-level institutional delivery (AOR: 3.93; 95%CI: 1.35–11.50) were the significant determinant factors of incomplete immunization in Ethiopia. Conclusion Young maternal age, family size, inadequate ANC, rural residence, not utilizing PNC services, and poor wealth status were the individual level determinants of incomplete immunization. Low and moderate level of ANC services utilization, and low community level institutional delivery service utilization were the factors determining incomplete immunization at the community level. Therefore, the health decision makers better to be committed to design strategies to enhance complete immunization coverage and maternal and child health services.